2020
DOI: 10.1371/journal.pone.0239646
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and fear of COVID-19 during the Rapid Rise Period in Bangladesh

Abstract: The study aims to determine the level of Knowledge, Attitude, and Practice (KAP) related to COVID-19 preventive health habits and perception of fear towards COVID-19 in subjects living in Bangladesh. Design: Prospective, cross-sectional survey of (n = 2157) male and female subjects, 13-88 years of age, living in Bangladesh. Methods: Ethical approval and trial registration were obtained before the commencement of the study. Subjects who volunteered to participate and signed the informed consent were enrolled in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
144
10
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 16 publications
26
144
10
8
Order By: Relevance
“…More specifically, females were found to have significantly higher levels of emotional eating, which is in line with the findings of previous empirical studies (e.g., Larsen et al 2006). It was also found that females reported higher levels of fear of COVID-19, which has also been found in other recent studies (e.g., Broche-Perez et al 2020;Hossain et al 2020;Sakib et al 2020). Therefore, it appears that the COVID-19 pandemic has emotionally affected females more negatively than males.…”
Section: Discussionsupporting
confidence: 90%
“…More specifically, females were found to have significantly higher levels of emotional eating, which is in line with the findings of previous empirical studies (e.g., Larsen et al 2006). It was also found that females reported higher levels of fear of COVID-19, which has also been found in other recent studies (e.g., Broche-Perez et al 2020;Hossain et al 2020;Sakib et al 2020). Therefore, it appears that the COVID-19 pandemic has emotionally affected females more negatively than males.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the respondents (72.9%) have confidence that Ethiopia can win the battle against COVID-19. This finding is in line with KAP study reports from China, Malaysia, Bangladesh, and India, 22 , 25 , 27 , 33 which reported high levels of positive attitudes towards combating the pandemic. The authors in these previous studies attributed the positive attitudes to the drastic measures taken by their governments (such as traffic limits and the lockdown of cities and counties) in mitigating the spread of the virus.…”
Section: Discussionsupporting
confidence: 90%
“…The possible reason for this discrepancy might be the fact that nearly all participants in these previous studies possess an academic degree or higher; and would actively grasp knowledge, respond actively to the severe condition of the pandemic and the overwhelming news reports, by collecting information from reliable sources such as official health related websites. Moreover, the magnitude of poor knowledge (48.7%) in this study was found to be higher than study reports from Kenya, 23 USA, 24 Bangladesh, 25 and China, 26 which is mainly attributed to differences in access for electricity and internet for accessing social media and other reliable source of information.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Findings from the current study revealed that female study participants had shown a higher likelihood of having low level of knowledge (AOR = 32, 95% CI: 7.66, 133.7, P<0.001). On the contrary, a comparable knowledge level was reported among males and females from a study conducted in Bangladeshi [ 40 ] which might be attributable to the presence of good educational support for females in the country. Whereas, like many other developing countries, educational support for females in Ethiopia has not been well developed yet.…”
Section: Discussionmentioning
confidence: 71%